Autogenous bone grafts and titanium mesh-guided alveolar ridge augmentation for dental implantation - Ming-Dih Jeng; Chun-Pin Chiang (Elsevier, 2020)
Background/purpose: Alveolar bone deficiency is sometimes found in the patients who need dental implantation. This study used autogenous bone grafts and titanium mesh-guided alveolar ridge augmentation for the patients with alveolar bone deficiency but requiring dental implantation. Materials and methods: In this study, autogenous bone grafts and titanium mesh-guided alveolar ridge augmentation was performed in four patients with different situations of alveolar bone deficiency. The titanium mesh was used as the barrier membrane and provided support to the compartment which was filled with calcium sulfate materials. Autogenous bone fragments harvested from adjacent implant osteotomy or from cortical bone of the recipient site were spread on the external surface of titanium mesh as the resources of osteoblasts for new bone formation. Results: Four months after above-mentioned procedures, cone-beam computed tomography showed adequate alveolar bone formation. The titanium mesh was removed and dental implant was placed in the augmented alveolar ridge at the same time. We found that secondary bone graft combined with autogenous bone and inorganic bovine bone were covered by the pseudo-periosteum and suitable for dental implantation in our four patients. The implants were submerged for 3-4 months till uncovering, and then the prostheses were delivered one month afterwards with successful clinical outcomes. Conclusion: The clinical outcomes of our four patients indicate that the vital autogenous bone grafts and the titanium mesh possess the ability to induce and guide new bone formation in four months and can be successful used for alveolar ridge augmentation and subsequent dental implantation.